Sensibilidade do BRAMS para descrição de chuva e temperatura, no nordeste do Rio Grande do Sul, para diferentes resoluções espaciais - Teichrieb, Claudio Alberto (2008)
This work presents a comparative study between precipitation and air temperature measurement observed at a wether station, located in Veranópolis RS, with data obtained from the BRAMS (Brazilian Regional Atmospheric Modeling System)atmospheric model with different spatial resolutions (5, 10 and 20 kilometers). The data used in this study collected in northeastern Rio Grande do Sul are the precipitation and temperatures (maximum, minimum and average). The period of data were analyzed six months, three in winter (June, July and August, 2007) and three months in summer (December 2007 and January and February 2008). The results show that the numerical model gets the best results of precipitation in the grid of 20 km, and the temperature is well reproduced in three grid.